Representaciones sociales del consumo de drogas en un contexto universitario, Medellín, Colombia, 2000 (2012)
ABSTRACT: To identify and characterize the social representations of drug use in a university context. Methodology: a framework was built by collecting the contributions of symbolic interactionism, interpretive ethnography, and textual analysis. Data collection was performed through 27 semistructured interviews and 7 focus groups. Likewise, the Reading Paradigm, proposed by a cultural hermeneutics of anthropological nature, was used as an analysis technique. Results and discussion: we observed social representations such as drug use as a socializing element facilitating social relations and as an element that gives meaning to life by putting the subject in a context where he or she is accepted. Conclusion: certain socially constructed forms of knowledge appear in the signifiers of drugs. They generate, through the functions of social representations, satisfiers that make it possible, through communication, to construct languages that shape the identity within the group and favor adaptation to the social environment of the university.